Evidence on the usefulness of management accounting systems in integrated manufacturing environment - Ismail, Kamisah; Isa, Che Ruhana; Mia, Lokman (Emerald, 2018)
Purpose: This paper aims to report the results of a study investigating the mediating role of managerial use of management accounting system (MAS) information in the relationship between integrated manufacturing practices (IMPs) and organisational performance (OP). IMP comprises three manufacturing practices, namely, just in time (JIT), total quality management (TQM) and advanced manufacturing technologies (AMTs). Design/methodology/approach: Using a mailed questionnaire, the data were gathered from senior managers working in 110 manufacturing firms listed in the Federation of Malaysian Manufacturers (FMM) Directory. Partial least square (PLS) was used to analyse the data. Findings: The results reveal that the relationship between IMP and OP exists via managerial use of MAS information, that is, adoption of IMP is positively associated with managerial use of MAS information, which in turn, is positively associated with the performance. In other words, managerial use of MAS information plays a significant role in linking adoption of IMP with OP. Originality/value: The use of MAS information in integrated manufacturing environment is found to assist firms in improving performance. Prior research on the IMP–OP relationship reports mixed (inconclusive) results. The authors contend that a possible reason for such results reported in prior studies is that the studies did not investigate the relationship between OP and IMP comprising each of the three manufacturing practices and performance as proposed by Dean and Snell (1991).